2022
DOI: 10.3390/su14052899
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urban Spatial Resilience and Its Influencing Factors: Case Study of the Harbin–Changchun Urban Agglomeration in China

Abstract: This study constructs a framework for evaluating urban spatial resilience based on five dimensions: scale, intensity, morphology, function, and benefit. Likewise, it empirically analyzes the spatial differences and influencing factors of urban spatial resilience in the Harbin–Changchun urban agglomeration from 2000 to 2020. Overall, the spatial resilience of the Harbin–Changchun urban agglomeration declined from 2000 to 2019. In addition, its ability to resist external disturbances weakened. The five dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Public space is the main place where residents work and live and is an important part of urban space (as shown in Figure 4). e public space that concentrates on the urban context and public activities can fully demonstrate the city's heritage, charm, and vitality [16]. With the continuous acceleration of the urbanization process, driven by the short-sighted construction goals, the problems of monotony and low-quality urban space have become increasingly prominent, and the original spatial characteristics and scales have disappeared.…”
Section: E Spatial Value Of Urban Contextmentioning
confidence: 99%
“…Public space is the main place where residents work and live and is an important part of urban space (as shown in Figure 4). e public space that concentrates on the urban context and public activities can fully demonstrate the city's heritage, charm, and vitality [16]. With the continuous acceleration of the urbanization process, driven by the short-sighted construction goals, the problems of monotony and low-quality urban space have become increasingly prominent, and the original spatial characteristics and scales have disappeared.…”
Section: E Spatial Value Of Urban Contextmentioning
confidence: 99%
“…Thirdly, by exploring the influencing factors of urban resilience in the study area, this paper finds that the level of openness has a negative impact on urban resilience. The study by Ma et al (2022) [55] also confirmed this finding, arguing that the level of opening to the outside world has a negative impact on inland cities. This is mainly due to the relatively low level of opening to the outside world in most inland cities, and the relatively single and fragile economic system.…”
Section: Theoretical Contributionmentioning
confidence: 78%
“…Greening coverage rate of built-up area (%) [52] + Per capita green space area in municipal area (m 2 ) [53] + Industrial wastewater discharge per unit GDP (t) [54] -Industrial sulfur dioxide emission per unit GDP (t) [54] -Industrial smoke (dust) emission per unit GDP (t) [54] -Centralized treatment rate of domestic sewage (%) [55] + Comprehensive utilization rate of industrial solid waste (%) [52] +…”
Section: Ecological Resiliencementioning
confidence: 99%
“…This plan was concerned with upgrading the industrial structure, transforming the economic system, resolving the issue of employment growth, promoting the development of regional economic integration [38], enabling sustainable development of rural agriculture in the three northeastern provinces [39], and accelerating urbanization [40]. In addition, as a result of the national revitalization strategy and other policies, more and more scholars were able to shift their focus on the highquality development of Northeast China [41][42][43][44][45]. In response to the national high-quality development strategy, Northeast China is facing huge challenges and opportunities, thus contributing to the study of spatial quality in Northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accelerate the revitalization of Northeast China and cause new breakthroughs, high-quality research on the Northeast China is particularly important. Thus far, scholars have only examined the development quality of Northeast China through the development characteristics of the entire city, ignoring the development quality of regional units [41][42][43][44][45]. This study differs from other scholars' research on the quality of urban macro time or the quality of the whole city but emphasizes the importance of spatial quality.…”
Section: Introductionmentioning
confidence: 99%